2016
DOI: 10.1177/0266242615612534
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education and entrepreneurial intention: Do female students benefit?

Abstract: This article explores links between entrepreneurship education (EE) participation, alertness and risk-taking skills and the intensity of entrepreneurial intention relating to becoming an entrepreneur. Guided by insights from human capital and socially learned stereotypes theories, we conceptualize and test novel hypotheses that consider the potential moderating effect of gender and participation in EE. Business students participating in EE modules were compared with engineering students excluded from such prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
159
3
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(184 citation statements)
references
References 107 publications
16
159
3
6
Order By: Relevance
“…Other authors have found that for females, having a role model can help boost their entrepreneurial self-efficacy (Barnir et al, 2011). In any case, our study provides further support to account for gender heterogeneity in future work (Westhead and Solesvik, 2016).…”
Section: Research Implicationssupporting
confidence: 77%
“…Other authors have found that for females, having a role model can help boost their entrepreneurial self-efficacy (Barnir et al, 2011). In any case, our study provides further support to account for gender heterogeneity in future work (Westhead and Solesvik, 2016).…”
Section: Research Implicationssupporting
confidence: 77%
“…EE the students with self-confidence, enterprise skills and knowledge are assumed to be able to deal with uncertainty, address social and institutional factors, and make informed decisions. Students are provided with theory, techniques and tools to take risks, and with new approaches to collect and analyse information (Westhead & Solesvik, 2016). Welsh et al (2016) stated that entrepreneurship education at university must develop proper attitudes, motives, intentions and grit to meet failure with a determination to start all over again and win.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…In several other studies, this relationship between education and entrepreneurship has been discussed within the effects of some moderator variables. Westhead and Solesvik (2015) have examined the positive role of entrepreneurship education on intentions and also considered the gendered ascriptions and its moderating effect. In addition to gender, type of courses, field of study, self-efficacy or past entrepreneurial experience have been evaluated as moderator variables in several studies (Fayolle et al 2006;Piperopoulos and Dimov 2015;Teixeira and Forte 2016).…”
Section: Literature Reviewmentioning
confidence: 99%